The effectiveness of the communication strategies adopted to eradicate corruption in Sarawak: A case study of Society Education Unit, Anti-Corruption Agency, Sarawak / Jutim Nyagam - Nyagam, Jutim (2002)
Combating corruption and abuse of power effectively does not solely depend upon the enforcement of laws, on the contrary, it requires a more concerted, planned and comprehensive approach inclusive not only the anti-corruption aspects but also those of efficiency, transparency, integrity, and accountability in the government's administration. Presently there is no universal definition of what is corruption; so as it's meaning and types of corruption it varies from country to country. As in the Laws of Malaysia, Section 2 of the Anti-Corruption Act 1997 (Act 575), corruption is interpreted as gratification. Gratification means money, donation, loan, fee, reward, valuable security, property, any office, dignity, employment, contract of employment or services, payment, any valuable consideration of any kind, any discount, commission, rebate, bonus, any forbearance to demand any money, any other service or favor of any description, any offer, any undertakings or promise.